SELEKSI INDUK KAMBING PERANAKAN ETAWAH BERDASARKAN NILAI MOST PROBABLE PRODUCING ABILITY BOBOT SAPIH DI KELOMPOK TANI MARGARINI - O, Yunanda; ., Sulastri; M., Hamdani (JURNAL ILMIAH PETERNAKAN TERPADU, 2013)
A survey to determined weaning weight, repeatability, and MPPA using 60 Ettawah Crossbreeddoe were held on Kelompok Tani Margarini, Sungai Langka Village, Gedong Tatanan SubDistrict, Pesawaran Regency. Data were taken from first and second offspring record onDecember 23rd, 2012, to January 17th, 2013.The corrected weaning weight, repeatibility, and MPPA resulted, i.e: 21,58 ± 1,03 kg; 0,31; and21,58 ± 0,49 kg, respectively. The best 5 MPPA were showed by doe number P1 (22,41 kg); G1(22,34 kg); B2 (33,232 kg); P2 (22,27 kg); and F1 (22,25 kg). The result also showed that 50% ofdoe have higher MPPA than that of the average.